2011
DOI: 10.1016/j.cyto.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3: A point of convergence for the host inflammatory response

Abstract: The phosphatidylinositol 3-kinase (PI3K) pathway has been shown to play a central role in regulating the host inflammatory response. Recent studies characterizing the downstream effector molecules within the PI3K pathway have identified that the serine/threonine kinase, glycogen synthase kinase 3 (GSK3), plays a pivotal role in regulating the production of pro-and antiinflammatory cytokines. In innate immune cells, GSK3 inactivation augments anti-inflammatory cytokine production while concurrently suppressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
199
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(202 citation statements)
references
References 128 publications
3
199
0
Order By: Relevance
“…Studies in our laboratory have shown that glycogen synthase kinase (GSK)-3b has a suppressive role on SHP2 phosphorylation, while pharmacologically inhibiting GSK-3b facilitated SHP2 activation followed by SHP2-mediated IFN-g resistance (36,65). Notably, in H. pylori infection, PI3K/Akt signaling may inactivate GSK-3b followed by b-catenin stabilization to promote gastric tumorigenesis (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in our laboratory have shown that glycogen synthase kinase (GSK)-3b has a suppressive role on SHP2 phosphorylation, while pharmacologically inhibiting GSK-3b facilitated SHP2 activation followed by SHP2-mediated IFN-g resistance (36,65). Notably, in H. pylori infection, PI3K/Akt signaling may inactivate GSK-3b followed by b-catenin stabilization to promote gastric tumorigenesis (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified GSK3 as a point of convergence for numerous cell-signaling pathways involved in a multitude of cellular physiological processes including development, cell cycle, differentiation, motility, microtubule function, apoptosis, adhesion, and inflammation (Doble and Woodgett 2003;Jope and Johnson 2004;Kockeritz et al 2006;Wang et al 2011c) (Fig. 1).…”
Section: What Is Gsk3 and How Does It Work?mentioning
confidence: 99%
“…It has been reported that GSK3b plays a central role in inflammation control by regulating the innate and adaptive immune responses (Wang et al 2011c). Since the pivotal role of inflammation in the development of cancer has been established, we will discuss the effect of inflammation in the development of EC and how GSK3b contributes to this process via regulating the activity and expression of inflammation mediators.…”
Section: Potential Involvement Of Gsk3 In the Progression Of Ec Via Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The proapoptotic and proinflammatory properties of GSK-3 have also been demonstrated in various animal models of inflammation, including experimental lung injury, shock, spinal cord trauma, arthritis, ischemia/reperfusion injury, infection, asthma, colitis, renal failure, and hepatotoxicity (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). GSK-3 is currently a known regulator of IFN-g signaling and is involved in IFN-g-induced inflammatory activation (51)(52)(53)(54)(55)(56)(57)(58)(59). Previous studies performed by ourselves and others identified a proinflammatory role for GSK-3 and found that inhibiting GSK-3 provides cellular protection against IFN-g (54-56)-, TNF-a (60)-, and LPS-induced inflammation in vitro (61)(62)(63) and multiple organ failure in vivo (46,47,49,63).…”
mentioning
confidence: 99%